Assessment of utility of Siriraj Stroke Score (SSS) in stroke patients of Pt. BD Sharma PGIMS hospital, Rohtak, India (Medical Journal of Indonesia, 2001)
India has predominantly poor rural population where brain CT scan, most often advised investigation in patients of stroke, may not always be available, hence Indian physician in such setting base his diagnosis on bed side sign evaluation for which Siriraj Stroke Score (SSS) could be helpful. Objective of study: to assess the utility of SSS in patients of stroke. Methodology: sixty subjects of stroke were evaluated on SSS and 'probable' diagnosis so made was compared with CT scan's (brain) 'certain' diagnosis. Main findings: by using SSS, the probable bedside diagnosis was cerebral infarct (score < -1) in 32 subjects and cerebral haemorrhage (score > +1) in 24 subjects while 4 subjects had indeterminant score (-1 to +1). Fifty subjects had their probable diagnosis matched with brain CT scan certain diagnosis. The above findings showed that SSS had 93.7% sensitivity, 76.6% specificity, 81.2% positive predictive value, 92% negative predictive value with an overall accuracy as 93.7% for diagnosis of cerebral infarction. For patients of cerebral haemorrhage the sensitivity was 83.3%, specificity was 92.5%, positive predictive value was 86.9%, negative predictive values was 92.5% with overall accuracy as 83.3%. Principal conclusion: physicians in the rural settings may find SSS to be quite useful in the management of stroke especially where more sophisticated radiological investigations may not be available for confirmation of diagnosis due to high cost or attended due to transportation risk. (Med J Indones 2007; 10: 164-8)